A systematic approach to the formation of quality and environmental safety of biofertilizer from digestate - Sipko, Iryna; Ablieieva, Iryna (Видавництво Львівської політехніки, 2024)
The use of anaerobic digestate as a biofertilizer is quite promising in terms of soil protection technologies in view of the reduction of environmental risks from the use of mineral fertilizers and the positive impact on soil productivity, improvement of their quality and restoration of the humus layer. However, anaerobic digestion does not ensure the complete absence of environmental hazards due to a certain probability of heavy metals, pharmaceutical substances, and pathogenic microorganisms entering the soil with biofertilizer. The article is aimed at determining effective methods of processing raw materials and digestate, as well as technological approaches for obtaining biofertilizer from digestate for use in geosphere protection technologies. The methodological basis of the study was a meta-analysis based on scientific publications within the framework of a systematic approach to the formation of the quality and ecological safety of fertilizer from digestate. It was established that the type of substrate initially affects the content of nutrients and pollutants, but the use of methods of pretreatment of raw materials, thermal and chemical, has the potential to balance the ratio of NPK and remove heavy metals. The most relevant is the choice of digestate separation technology. Thus, it is essential to apply post-treatment methods to raw digestate and its individual fractions. The creation of granulated organo-mineral fertilizers and the production of biochar from the solid fraction of digestate are suggested as environmentally safe products for soil protection technologies.
Keywords: anaerobic digestion; granular biofertilizer; heavy metals; micronutrients; soil protection technologies; digestate post-treatment